Playing - Medium for Understanding, Interpreting and Transforming Immediate Reality - Šagud, Mirjana (Array, 2014)
The fundamental study or conceptualization of the development and learning of early and preschool aged children necessarily takes into consideration children’s play as a medium that allows imaginative transformation of the child’s observation and understanding of immediate reality. While playing, the reality is metaphorically interpreted and presented with the help of alternative scenarios, while the actual events and experiences are being re-transformed and they vary from the child’s perspective. Playing is a social practice (it occurs in cooperation with others and/or with the help of conditions that others create), and as such it is a specific mode of a socio-cultural reality in which the child, due to its incapability of total understanding and only partial participation, objectively reflects its real space and it interprets and ‘’changes‘’ it a lot more. A child reconstructs its experience and day to day reality in an imaginary world of play, but almost always including recognizable social rules and under control of events. The daily authentic institutional context should be arranged in a way that it allows free elaboration and expression of children’s experiences and which builds and develops social capacities that will allow better participation in various social groups. Playing – the medium for understanding, interpreting and transforming immediate reality